2009
DOI: 10.1007/s00213-009-1474-y
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal from free-choice high-fat high-sugar diet induces craving only in obesity-prone animals

Abstract: The results show for the first time that withdrawal from free-choice HFHS induces craving that is specific to the OP animals and suggests that OP individuals may have withdrawal symptoms that are similar to those induced by addictive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 47 publications
3
60
0
5
Order By: Relevance
“…High-fat food withdrawal and reward S Sharma et al that contribute to food cravings following HFD withdrawal, 20 removal of high-fat food following long-term intake is sufficient to enhance motivation and cravings for palatable foods. In addition to increasing motivation for palatable food, HFD removal potentiated anxiety-like behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-fat food withdrawal and reward S Sharma et al that contribute to food cravings following HFD withdrawal, 20 removal of high-fat food following long-term intake is sufficient to enhance motivation and cravings for palatable foods. In addition to increasing motivation for palatable food, HFD removal potentiated anxiety-like behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Cottone et al [16][17][18] found that withdrawal from extended, intermittent access to palatable food increases anxiety and decreases effortbased responding for less palatable chow, an effect linked to elevated corticotrophin-releasing factor receptor-1 (CRF-R1) signalling in the amygdala. 19 HFD removal is reported to increase operant responding for sucrose rewards in obesity-prone but not obesity-resistant rats, 20 however, it is not known if withdrawal from chronic high-fat feeding increases anxiety and palatable food reward, independent of genetic factors that enhance susceptibility to weight gain and which neurobiological changes are involved.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, OP animals have gained more weight than the OR and control group, even though there were no significant differences in food intake between the experimental groups. It is also noteworthy that total amount of consumed calories did not correlate with body weight increase [82].…”
Section: Pre-clinical Models Of Binge Eatingmentioning
confidence: 98%
“…It has been hypothesized that individuals expressing the Taq1 A1 allele are more susceptible to seek and consume palatable food as a form of compensatory behaviour [71]. Individual vulnerabilities have also been observed in rodents: the motivation to consume palatable food is more pronounced in obesity-prone rats [73], and rats more sensitive to the incentive properties of palatable food are significantly more sensitive to the reinforcing effect of cocaine [74].…”
Section: Food Addiction: Classic Substance Dependence?mentioning
confidence: 99%